A model of public sector e-services development efficiency as a sustainable competitive advantage - Asta Valackiene; Jovita Giedraitiene (Administrative Sciences, 2024)
This study aims to explore the links between the efficiency of public sector e-services and sustainable competitive advantage. In line with the emerging approach, the instrumental case study design and the mixed research strategy were used as the most appropriate methodology to answer the general research question that was raised for this study. In this context, we present the positive experience that we have discovered via the Lithuanian case study. A unified model of evaluation of the e-services development system in the public sector was developed. The model explains the application of various e-services development systems methodologies and methods in the public sector and underpins the platform for the interaction of efficiency and sustainable competitive advantage processes. The model developed helps to make the assessment of e-services more effective and demonstrates a personalised outcome that can be applied by other public sector organisations. The paper discusses the efficiency trends in the development of e-services in the public sector in order to achieve Sustainable Development Goals, as well as distinguishes and highlights procedural steps that help to improve the development of e-services and sustainable competitive advantage.
Keywords: 350; advantage; efficiency of e-service; Lithuania; model; public sector; sustainable competitive